PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN MENGGUNAKAN BOOKLET SPINAL ANESTESI TERHADAP KECEMASAN PADA PASIEN SECTIO CAECAREA - Agus Sarwo Prayogi (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2021)
Abstract Preoperative anxiety often associated with incorrect understandings of the surgery or the lack of information about the events that will be experienced by the patient before, during and even after the surgical procedure. Surgery is sectio caesarea a potential or actual threat to the integrity of the person who can evoke physiological stress reactions and psychological health education is needed on spinal anesthesia to patients sectio caesarea pre-anaesthesia using the booklet. The purpose of research known effect of health education using booklet spinal anesthesia to anxiety in patients sectio caesarea. This type of research quasi-experiment without a control group. The sampling techniques in this study using purposive sampling, using questionnaires APAIS sample of 24 respondents. Data were analyzed using paired t-test. Before the results are given health education using booklet spinal anesthesia most respondents experiencing severe anxiety before undergoing anesthesia. After being given health education using booklet spinal anesthesia most respondents experiencing mild anxiety. Results of paired t-test p-value 0,000 <0,05. There was a significant effect of health education using booklet giving spinal anesthesia to anxiety in patients sectio caesarea.Keywords: booklets, anxiety, sectio caesarea, health education.